Enhancing the performance of distance protection relays using interactive control system - Hassan S. Mohamed; M. Mehanna; El-Saied Osman (Institute of Advanced Engineering and Science, 2019)
Recently improvement of automation systems for electrical power system network became essential for increasing the realiability of power transmission during any disturbance. In a substations the setting of Distance Relays (DRs) are set manually which depends on human experience which may be led to undesirable operation. Any power transmission system may subjected to shortens and loss of adjusting its protection setting, DRs in protection systems are responsible for protected a High voltage transmission lines from short circuit, power swing, and load encroachment, A proposes automation system architecture is introduced to cover the setting and coordination of protection scheme based on DIgSILENT power factory, SIMATIC manger, and WinCC programs.